A Modification of Atomic Orbital Theory and Its Application to $(1snl)^1L^{π}$ and $(nl^2)L^{π}$ Excited States of He-Like Ions (Journal of Atomic and Molecular Sciences, 2010)
A modification of the Slater's atomic orbital theory (AOT) is presented in this paper and applied to the calculation of energies for (1$sns$)$^1S^e$, (1$snp$)$^1P^o$, (1$snd$)$^1D^e$ and ($ns^2$)$^1S^e$, ($np^2$)$^1D^e$, ($nd^2$)$^1G^e$, ($nf^2$)$^1I^e$, ($ng^2$)$^1K^e$, ($nh^2$)$^1M^e$ excited states of He-like ions up to $Z$ = 12. The inadequacy of Slater's AOT for excited states of the atomic systems is discussed. The results obtained in the present work are in good agreement with available experimental and theoretical results.